Review of methods for detecting glycemic disorders. (July 2020) - Bergman, Michael; Abdul-Ghani, Muhammad; DeFronzo, Ralph A.; Manco, Melania; Sesti, Giorgio; Fiorentino, Teresa Vanessa; Ceriello, Antonio; Rhee, Mary; Phillips, Lawrence S.; Chung, Stephanie; Cravalho, Celeste; Jagannathan, Ram; et al.
Highlights: A 1-hour plasma glucose (1-h PG) ≥ 155 mg/dl (8.6 mmol/L) during an oral glucose tolerance test (OGTT) can identify normal glucose tolerant (NGT) individuals at high-risk for type 2 diabetes (T2D). A 1-hour, non-fasting, 50 g Glucose Challenge Test (GCT) performed during a routine health care visit has potential for practical screening of glucose disorders. The shape of the glucose curve reflects the cumulative effect of insulin sensitivity and response on glucose concentrations with prospective studies warranted to evaluate its prognostic utility. The continuous glucose monitor (CGM) has facilitated insight into the pathophysiology of prediabetes and phenotypes of T2D and holds promise for detecting glycemic disorders. Metabolomic profiling including amino acids, lipids, carbohydrates and other metabolites may be useful for early diagnosis of glycemic disorders. Non-classical markers for assessing glycemic disorders including fructosamine, glycated albumin, and 1, 5-anhydroglucitol that evaluate shorter periods of glucose exposure than HbA1c have potential use as adjunctive tools. Abstract: Prediabetes (intermediate hyperglycemia) consists of two abnormalities, impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) detected by a standardized 75-gram oral glucose tolerance test (OGTT). Individuals with isolated IGT or combined IFG and IGT have increased risk for developing type 2 diabetes (T2D) and cardiovascular disease (CVD). Diagnosing prediabetes early and accurately is critical in order to refer high-risk individuals for intensive lifestyle modification. However, there is currently no international consensus for diagnosing prediabetes with HbA1c or glucose measurements based upon American Diabetes Association (ADA) and the World Health Organization (WHO) criteria that identify different populations at risk for progressing to diabetes. Various caveats affecting the accuracy of interpreting the HbA1c including genetics complicate this further. This review describes established methods for detecting glucose disorders based upon glucose and HbA1c parameters as well as novel approaches including the 1-hour plasma glucose (1-h PG), glucose challenge test (GCT), shape of the glucose curve, genetics, continuous glucose monitoring (CGM), measures of insulin secretion and sensitivity, metabolomics, and ancillary tools such as fructosamine, glycated albumin (GA), 1, 5- anhydroglucitol (1, 5-AG). Of the approaches considered, the 1-h PG has considerable potential as a biomarker for detecting glucose disorders if confirmed by additional data including health economic analysis. Whether the 1-h OGTT is superior to genetics and omics in providing greater precision for individualized treatment requires further investigation. These methods will need to demonstrate substantially superiority to simpler tools for detecting glucose disorders to justify their cost and complexity.